Promotion effects of mono‐2‐ethyhexyl phthalate (MEHP) on migration and invasion of human melanoma cells via activation of TGF‐β signals. (30th October 2019) - Fan, Pengju; Li, Zhen; Zuo, Chenchen; Fang, Man
Abstract : Malignant melanoma is one of the most leading forms of skin cancer associated with a low patient survival rate. There is an urgent need to illustrate risk factors that can trigger the motility of melanoma cancer cells. Our present study revealed that mono‐(2‐ethylhexyl)phthalate (MEHP) exposure can significantly increase the in vitro migration and invasion of WM983A and A375 cells. Among the tested cytokines, MEHP can increase the expression of transforming growth factor β (TGF‐β). Inhibition of TGF‐β via its neutralization antibody can attenuate MEHP‐induced cell migration and invasion. Further, upregulation of TGF‐β mediated MEHP‐induced activation of Smad signals and upregulation of Snail in melanoma cells. Blocking the TGF‐β/Smad signal pathway can attenuate MEHP‐induced cell migration. Estrogen receptor α (ERα) was essential for MEHP‐induced expression of TGF‐β. In addition, MEHP can increase the expression of ERα in melanoma cells. Collectively, our study found that MEHP can stimulate the progression of melanoma via TGF‐β signals. Significance: Mono‐(2‐ethylhexyl)phthalate (MEHP) is the active and most toxic metabolite of di(2‐ethylhexyl)phthalate (DEHP). Our present study revealed that MEHP can trigger the in vitro migration and invasion of melanoma cells via upregulation of TGF‐β/Snail signals. It revealed that daily exposure to MEHP might be a risk factor for melanoma patients.